Formulation development and evaluation of mouth dissolving film of domperidone - Pratikkumar Joshi; Harsha Patel; Vishnu Patel; Rushi Panchal (Wolters Kluwer Medknow Publications, 2012)
The present investigation was undertaken with the objective of formulating mouth dissolving film(s) of the antiemetic drug Domperidone to enhance the convenience and compliance by the elderly and pediatric patients. Domperidone is a drug of choice in case of nausea and vomiting produced by chemotherapy, migraine headaches, food poisoning and viral infections. It causes dopamine (D2 and D3) receptor blockage both at the chemoreceptor trigger zone and at the gastric level. It shows high first pass metabolism which results in poor bioavailability (10-15%). In view of high first pass metabolism and short plasma half-life it is an ideal candidate for rapid release drug delivery system. The solid dispersions of Domperidone were prepared with the use β-cyclodextrin in various ratios (1:1, 1:2, 1:3) and solubility study was performed to determine the ratio in which solubility of Domperidone was highest (1:3). The selected solid dispersions were then utilized for the preparation of film by solvent casting method utilizing HPMC E15 as a film forming agent and PEG-400 as plasticizer. Five formulae were prepared and were evaluated for their in vitro dissolution characteristics, in vitro disintegration time, and their physico-mechanical properties. The promising film (F1) showed the greatest drug dissolution (more than 75% within 15 min), satisfactory in vitro disintegration time (45 sec) and physico-mechanical properties that are suitable for mouth dissolving films.